Socialization and Training of Solar Power Generation (PLTS) at SD Negeri Tambakharjo Semarang - Adhi Kusmantoro; Irna Farikhah (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2022)
SD Negeri Tambakharjo Semarang uses PLN electricity with low installed power. The school is located in an area that has a total photovoltaic output power and solar radiation intensity of 1,486 Mwh/year and 1953.3 Kwh/m2/year.   The average output power per day of photovoltaic (solar panels) in October and November 2021 was 4551 Wh and 3778 Wh.  Therefore, the purpose of community service is to socialize the use of solar power plants (PLTS) through learning activities (education) and solar pv training for students and school teachers. The methods used in this activity are divided into three stages. In the first stage, field observations were carried out to find problems related to the availability of electrical energy in schools. In the second stage, the implementation of community service includes the delivery of solar panel material with lectures, demos, and solar power plant system designs in schools. In the third stage, it is the stage of evaluation or feedback by providing questionnaires to participants. The results of this service activity provide information data on understanding of solar panels and batteries in the good category. For practical activities, it needs to be improved to be taught for students in grades 5 and 6, so that solar pv props are indispensable in the school.